A New Concept for Magnetic Capsule Colonoscopy Based on an Electromagnetic System. (26th March 2015) - Lucarini, Gioia; Ciuti, Gastone; Mura, Marco; Rizzo, Rocco; Menciassi, Arianna
Traditional endoscopy based on flexible endoscopes is reliable and effective, but poorly tolerated by patients; it also requires extended training by physicians. In order to reduce the invasiveness of these procedures, wireless passive capsule endoscopy has been proposed and clinically used during the past decade. A capsule endoscope with an active locomotion mechanism is desirable for carrying out controllable interactive procedures that are normally not possible using passive devices. Due to many difficulties in embedding actuators in swallowable devices, many researchers and companies have adopted an external magnetic field actuation solution. Magnetic resonance modified systems or permanent magnets are used to manoeuvre capsules remotely; however, both these cases present some limitations: magnetic resonance systems are bulky and expensive and permanent magnets are intrinsically unstable to control, and it is impossible to switch them off. Within this framework, the authors present the design and assessment of a magnetic system for endoscopic capsules based on an electromagnetic approach. In particular, the use of a single electromagnet was proposed and investigated: magnetic attraction, locomotion forces and magnetic torques were modelled for guaranteeing the reliable navigation of the capsule and based on these specifications, an electromagnet was designed, developed and experimentally evaluated. The results demonstrated the feasibility of the proposed approach for active locomotion capsule endoscopy.